PSYCHOLOGICAL DETERMINANTS OF EMOTIONAL INTELLIGENCE AND STRESS RESILIENCE IN THE EFFICIENCY OF PEDAGOGICAL ACTIVITY: THE CONTEXT OF TRAINING HIGHLY QUALIFIED PERSONNEL IN THE CONDITIONS OF GLOBALIZATION. (Universal International Scientific Journal, 2026)
This article is devoted to the study of the psychological determinants of emotional intelligence and stress resistance in ensuring the mental health of teachers and increasing the effectiveness of pedagogical activity in the process of training highly qualified personnel in the conditions of globalization. The study considers emotional intelligence as the ability of a teacher to understand himself and others, to manage them, and to adapt to the social environment. Stress resistance determines the ability of teachers to adapt to external pressures and difficulties. The article highlights innovative approaches - emotional intelligence development training, stress management techniques, psychological monitoring and team mentoring systems - as a means of increasing the effectiveness of pedagogical activity and supporting mental health in the process of training highly qualified personnel.
Keywords: : emotional intelligence, stress resistance, pedagogical activity effectiveness, psychological determinants, innovative approaches, training of highly qualified personnel, mental health.